Individuals living with cancer in turkey and the COVID-19 pandemic - Sert, Gürkan; Torun, Serap; Karatas, Mehmet; Gozderesi, Yakup; Okuyaz, Selda; Yalcın, Sibel Oner; Yıldırım, Gulay; Nazik, Sadık (Acta Bioethica, 2022)
The aim of this study is to determine the problems faced by individuals living with cancer (ILCs) in accessing health services during the COVID-19 pandemic in Turkey. This qualitative study’s sample consisted of 18 volunteer interviewees from 10 cancer-related patient associations in Turkey. Research data were collected by semi-structured interview method. Data collection and analysis were carried out simultaneously. In the sessions where all researchers participated together, the data were coded with a common view, and main and sub-themes were determined. In the analysis of the data the inductive thematic analysis method was applied. Information was gathered under two main themes: compliance with the measures taken and access to health services. Lack of information about nutrition, physical activity, psychological problems, caused by the lockdown and social distance measures taken within the scope of the pandemic should be accepted as problems within the scope of the right of individuals to access health, and additional programs should be prepared to minimize these. Cancer types should be considered in delaying diagnosis, treatment, and controls related to cancer, so that patients are not harmed at least or at all. It is important to ensure that patients do not hesitate to attend diagnosis, treatment, and controls with the anxiety of being infected with COVID-19, both in transportation to health facilities and in terms of preventing transmission in health facilities.